Types of Internet Activity and the Religious Commitment of American Adults. - Laderi, Jennifer O.; Uecker, Jeremy E. (Journal for the Scientific Study of Religion (John Wiley & Sons, Inc.), 2025)
This study addresses the ongoing debate surrounding the connection between Internet use and religious identity, belief, salience, and practices. Using data from the 2021 wave of the Baylor Religion Survey (N = 1248), we analyze the relationships between different types of Internet activity and religious outcomes. We find that time spent on online gaming is associated with a higher likelihood of holding atheist or agnostic beliefs and with lower levels of both private and public religiosity. In contrast, posting original content to social media is positively associated with personal scripture reading and religious attendance, suggesting that some forms of digital engagement may reinforce religious practices. Other activities, such as general social media use and video chatting, have no significant associations with religious commitment. Our findings suggest that the Internet and religiosity are not always at odds. Both Internet use and religion are multifaceted phenomena whose relationship varies depending on the nature of online engagement and the religious outcome in question.